Use of azelaic acid in the treatment of acne vulgaris in adolescents (Research, Society and Development, 2022)
The pathogenesis of acne is an involvement of some multifaceted processes within the pilosebaceous unit, giving room for bacterial overgrowth and inflammation. This usually happens in the pubertal transition period, when hormonal changes in the body alter the function of the pilosebaceous gland, with this, studies have shown that, in clinical cases, azelaic acid is effective and safe when applied to the specific location where acne is found. , and in the proper concentration. The aim of this study is to identify the benefits of azelaic acid in the treatment of acne vulgaris in adolescents, through data from the literature. It is an integrative literature review, which allows the summary of several published studies, allowing new knowledge and results of other research. The analysis of the data obtained was performed after organizing the selected articles in a table containing: author, theme, objective, methods, results, and year of publication. It can be concluded that azelaic acid has a positive effect in the treatment of acne vulgaris, when applied in the correct way, ideal amount and in a timely manner. It is very important to follow up with a professional, because the acid, despite promoting tolerable side effects, can cause greater dysfunctions if the type of acne, skin or lifestyle of the teenager is not analyzed.